Stress, autonomic imbalance, and the prediction of metabolic risk: A model and a proposal for research. (March 2018) - Wulsin, Lawson; Herman, James; Thayer, Julian F.
Highlights: Autonomic imbalance is associated with all eight major cardiovascular risk factors, including obesity and diabetes, and autonomic imbalance is a common feature of the biology of acute and chronic stress. Autonomic imbalance can be measured and treated by a variety of methods often used in primary care settings, making autonomic imbalance a potential target for preventive interventions for heart disease, diabetes, obesity, and metabolic risks in general. Adding clinical implications to the neurovisceral integration model, our proposal places autonomic imbalance in relationship to other contributing factors along the pathway from chronic stress to metabolic risk and provides a framework for longitudinal study design. Our review of eleven prospective human studies shows substantial evidence that autonomic dysregulation precedes and promotes the development of multiple metabolic risks and disorders. We propose priorities for research in four areas: a) further testing of components of the model in animals and humans, b) refining measurements of exposure variables, c) establishing risk thresholds for the key exposure variables, and d) testing prevention interventions. Abstract: Background: Devising novel prevention strategies for metabolic disorders will depend in part on the careful elucidation of the common pathways for developing metabolic risks. The neurovisceral integration model has proposed that autonomic imbalance plays an important role in the pathway from acute and chronic stress to cardiovascular disease. Though generally overlooked by clinicians, autonomic imbalance (sympathetic overactivity and/or parasympathetic underactivity) can be measured and modified by methods that are available in primary care. Method: This review applies the neurovisceral integration concept to the clinical setting by proposing that autonomic imbalance plays a primary role in the development of metabolic risks. We present a testable model, a systematic review of the evidence in support of autonomic imbalance as a predictor for metabolic risks, and specific approaches to test this model as a guide to future research on the role of stress in metabolic disorders. Conclusions: We propose that autonomic imbalance deserves consideration by researchers, clinicians, and policymakers as a target for early interventions to prevent metabolic disorders.